2015
DOI: 10.1631/jzus.b1400292
|View full text |Cite
|
Sign up to set email alerts
|

Mineral metabolism disturbances are associated with the presence and severity of calcific aortic valve disease

Abstract: Abstract:Objective: We investigated whether disturbance of calcium and phosphate metabolism is associated with the presence and severity of calcific aortic valve disease (CAVD) in patients with normal or mildly impaired renal function. Methods: We measured serum levels of calcium, phosphate, alkaline phosphatase (AKP), intact parathyroid hormone (iPTH), 25-hydroxyvitamin D (25-OHD), and biomarkers of bone turnover in 260 consecutive patients with normal or mildly impaired renal function and aortic valve sclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In the largest such study, 260 AS patients were compared with 164 age and sex matched controls. Stepwise increases in serum calcium, phosphate, PTH, alkaline phosphatase, and stepwise decreases in serum 25-OH vitamin D, were significantly associated with increasing severity of AS 40 .…”
Section: Relevant Pathophysiologymentioning
confidence: 88%
“…In the largest such study, 260 AS patients were compared with 164 age and sex matched controls. Stepwise increases in serum calcium, phosphate, PTH, alkaline phosphatase, and stepwise decreases in serum 25-OH vitamin D, were significantly associated with increasing severity of AS 40 .…”
Section: Relevant Pathophysiologymentioning
confidence: 88%
“…Increased serum calcium and phosphorus levels are associated with coronary artery disease, cerebrovascular events, peripheral artery disease, and heart valve calcification 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 . Furthermore, decreased serum fetuin-A and albumin levels are associated with the development of coronary artery disease and heart valve calcification 50 51 52 53 54 55 56 57 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Calcific aortic valve disease, which is considered to share similar biological processes with atherosclerosis, involves endothelial dysfunction, lipid infiltration, inflammation, oxidative stress and mineralization of aortic valves [ 7 ]. Previous studies have demonstrated an association of abnormal metabolism of calcium and lipid with the presence of CAVD [ 7 , 8 ]. Because increased Hcy levels can cause endothelial injury [ 9 ], Hcy has been hypothesized to initiate the inflammatory process and facilitate a series of reactions in CAVDs.…”
Section: Introductionmentioning
confidence: 99%